2015
DOI: 10.1039/c5sc00163c
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and optical control of electronic states in a single layer of switchable paramagnetic molecules

Abstract: Thermally and optically induced Valence Tautomeric interconversion has been observed for a monolayer of a cobalt–dioxolene complex on gold.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 62 publications
1
34
0
Order By: Relevance
“…The molecules at the surface suffer less chemical pressure, and may possibly exhibit a lower transition temperature. Indeed, when probed by X-ray absorption spectroscopy with the total electron yield detection mode that is extremely sensitive to the surface layer, a much higher ratio of HS molecules was detected compared with that obtained by magnetometry in the reported VT cobalt-dioxolene complexes [38][39][40] . However, the preliminary experiments showed that 1•0.5EtOH was very sensitive to X-ray exposure and exhibited irreversible X-ray-induced damage that hindered further investigations of the surface effect using this technique.…”
Section: Resultsmentioning
confidence: 93%
“…The molecules at the surface suffer less chemical pressure, and may possibly exhibit a lower transition temperature. Indeed, when probed by X-ray absorption spectroscopy with the total electron yield detection mode that is extremely sensitive to the surface layer, a much higher ratio of HS molecules was detected compared with that obtained by magnetometry in the reported VT cobalt-dioxolene complexes [38][39][40] . However, the preliminary experiments showed that 1•0.5EtOH was very sensitive to X-ray exposure and exhibited irreversible X-ray-induced damage that hindered further investigations of the surface effect using this technique.…”
Section: Resultsmentioning
confidence: 93%
“…Recently, more complex architectures, such as core–shell particles, multilayer films, hybrid plasmonic, and fluorescent SCO particles have been also synthesized attesting a certain degree of maturity of the field and providing scope for the development of multifunctional nanomaterials displaying synergistic effects. Let us mention also that conceptually related valence tautomeric and Jahn–Teller switch type molecule‐based nanomaterials have been also synthesized recently—raising similar fundamental questions and application ideas …”
Section: Introductionmentioning
confidence: 89%
“…More recently, the control of the charge distribution of VT complexes assembled on flat gold surfaces has been attained by Poneti and co-workers. 34 In this case, the authors synthesised a series of catechol-based VT complexes with different charge distributions of the ls-Co(III)Cat and the hs-Co(II)SQ tautomers and assembled them on gold surfaces through the thiol moiety previously introduced in the catechol ligand. In contrast to the results reported by Shultz et al, these authors observed that the charge distribution of the complexes as well as their entropydriven interconversion equilibria were not affected by surface grafting and that the VT behaviour of the bulk phase was quantitatively reproduced on the surface.…”
Section: Nanostructured Surfaces and Interfacesmentioning
confidence: 99%